The Role of Education in Tourism Development: Focus on Attractions, Amenities, and Accessibility - Ridho Rafqi Ilhamalimy; Achmad Husen Husen; SUPARNO SUPARNO SUPARNO; DONI SUGIANTO SIHOTANG; SURATMAN SURATMAN SURATMAN (BASKARA : Journal of Business and Entrepreneurship, 2025)
This study aims to develop a theoretical proposition concerning the role of education in tourism development based on the core components of attractions, amenities, and accessibility (commonly referred to as the 3A framework). The background of this research lies in the limited integration of educational strategies in shaping sustainable and competitive tourism sectors. Education is identified as a key factor in enhancing human resource capabilities, facility management, and accessibility planning—primarily through vocational training, curriculum development, and knowledge-based policy-making. The study employs a qualitative method using literature review and bibliometric analysis with the aid of Vosviewer software. The research offers a theoretical and historical analysis of how education supports tourism development by improving the quality and sustainability of attractions, enhancing the management and service standards of amenities, and increasing accessibility through inclusive policy frameworks and data-driven infrastructure planning. The findings suggest that the effectiveness of the 3A components is significantly influenced by the educational capacity and competencies of tourism stakeholders. This paper provides a conceptual foundation for future studies and recommends further empirical investigation using exploratory or confirmatory factor analysis. Future researchers are encouraged to examine the causal relationships between educational strategies and the enhancement of tourism infrastructure and services using quantitative and multilevel analytical methods.